Bacterial extracellular vesicles – brain invaders? A systematic review - Kaisanlahti, Anna; Salmi, Sonja; Kumpula, Sohvi; Amatya, Sajeen Bahadur; Turunen, Jenni; Tejesvi, Mysore; Byts, Nadiya; Tapiainen, Terhi; Reunanen, Justus (Frontiers in Molecular Neuroscience, 2023)
Introduction: Knowledge on the human gut microbiota in health and disease continues to rapidly expand. In recent years, changes in the gut microbiota composition have been reported as a part of the pathology in numerous neurodegenerative diseases. Bacterial extracellular vesicles (EVs) have been suggested as a novel mechanism for the crosstalk between the brain and gut microbiota, physiologically connecting the observed changes in the brain to gut microbiota dysbiosis. Methods: Publications reporting findings on bacterial EVs passage through the blood-brain barrier were identified in Pubmed and Scopus databases.The literature search yielded 138 non-duplicate publications, from which 113 records were excluded in title and abstract screening step. From 25 publications subjected to full-text screening, 8 were excluded. The resulting 17 publications were considered for the review. Discussion: Bacterial EVs have been described with capability to cross the blood-brain barrier, but the mechanisms behind the crossing remain largely unknown. Importantly, very little data exists in this context on EVs secreted by the human gut microbiota. This systematic review summarizes the present evidence of bacterial EVs crossing the blood-brain barrier and highlights the importance of future research on gut microbiota-derived EVs in the context of gut-brain communication across the blood-brain barrier.